Perception and Behaviour of Mutual Funds Investors In Indore, Madhya Pradesh - Vyas, Ravi; Moonat, Suresh Chandra (Indian Journal of Finance, 2012)
The concept of Mutual funds has been on the financial landscape for long in a primitive form. The story of the M F industry in India started in 1963, with the formation of the Unit Trust of India at the initiative of the Government of India and Reserve Bank. The launching of innovative schemes in India has been rather slow due to the prevailing investment psychology and infrastructural inadequacies. Risk averse investors are interested in schemes with tolerable capital risk and return over a bank deposit, which has restricted the launching of riskier products in the Indian Capital market. But this objective of the Mutual Fund industry has changed over the decades. For many years, funds were more of a service than a product, the service being professional money management. In the last 15 years, Mutual Funds have evolved to be a product. A competent fund manager should analyze investor behaviour and understand their needs and expectations, to gear up the performance of MFs to meet investors’ requirements. It is the time for mutual fund companies to understand the fund selection/ switching behaviour of the investors’ and to design the fund schemes according to the changing needs of consumers. The present study makes efforts in this regard to suggest ways to penetrate this mode of investment deep in the Indian society, and it also provides information regarding what the present investor expects.